Diakonia in a Gender Perspective. - Dietrich, Stephanie (Regnum Books International, 2016)
Gender perspectives play a core role when it comes to both the theory and practice of diakonia. This is the second book on diakonia published by Regnum Books. It follows up Diakonia as Christian Social Practice: An Introduction (2014). Many of the authors belong to VID Specialized University in Norway (Campuses in Oslo, Stavanger and Bergen).